Crack the C-Suite Code : How Successful Leaders Make It to the Top. - Frangos, Cassandra (Wharton Digital Press, 2018)
How can I reach the C-suite? That is the most common question Cassandra Frangos hears from the leaders she coaches. Many aspire to reach the C-suite, but the paths there are hard to find and difficult to follow. In Crack the C-Suite Code, Frangos demystifies the journey and offers a career playbook for anyone who aspires to the top spot.